REKONSTRUKSI MAKNA SUNNAH PERSPEKTIF MUHAMMAD SYAHRUR - Yuliana Jamaluddin (Farabi, 2017)
Shahrur distinguish between traditions to the Sunnah, because the Sunnah is a practical application (ijtihad) of the Prophet in embody divine treatise that revealed to him, while the tradition is a form of ijtihad Prophet verbalization. Shahrur Sunnah split into two, the Sunnah and the Sunnah Nabawiyya Rasuliyyah. Shahrur does not deny the existence of traditions as long as it is authentic, but he stressed the need for classification in accordance with the position of the Prophet's hadith, namely: as human beings, as a prophet, and as an apostle. The concept of Sunnah and Hadith classification offered by Shahrur actually not an idea that is really new, because there are some similarities with some of the previous figures. However, there is its own peculiarities that characterize the concept of Sunnah initiated by Shahrur, among which are the classifications made always followed by clear indicators, so the concept is applicable and systematic.